Detecção de patógenos periodontais em mães de bebês prematuros e/ou de baixo peso ao nascer - VASCONCELOS , Nayra Rodrigues de (2014)
The periodontal pathogens bacteria Prevotella intermedia (Pi), Fusobacterium nucleatum (Fn), Porphyromonas gingivalis (Pg), Treponema denticola (Td), Tannerella forsythia (Tf) and Aggregatibacter actinomycetemcomitans (Aa) may be associated with preterm and / or low birth Birth weight (NPT / LBW), since they have been found within the amniotic fluid of infants. The present study aims to estimate the possible relationship between periodontal pathogens in the oral cavity and the birth of Preterm Birth (PTB) and/or Low Birth Weight (LBW). It’s a case- control study with the subgengival biofilm samples were collected from four sites up deeper until 48 hours postpartum and were processes by Polymerase Chain Reaction (PCR) for presence the periodontal pathogens Prevotella intermedia (Pi), Fusobacterium nucleatum (Fn), Porphyromonas gingivalis (Pg), Treponema denticola (Td), Tannerella forsythia (Tf) e Aggregatibacter actinomycetemcomitans (Aa). The mothers were divided into case grup (babies weighing < 2500g and/or gestational age < 37 weeks) and control group (babies weighing ≥ 2500g and gestational age ≥ 37 weeks). Chi-square test and the measure of association obtained by Odds Ratio (OR) were used to estimate the association between the variables. Microbial analyses results showed no significant association between PTB and LBW with most periodontal pathogens in the oral cavity, even with association with the clinical presence of periodontitis. However, given the high presence of periodontal pathogens in the biofilm subgengival of recent mothers, it is suggested that the findings of this research serve as the basis for future studies on the pathophysiology involved in the relationship between periodontitis and PTB and/or LBW.